Arbuscular Mycorrhizal Fungi as Seed Coat of Soybean Grown on Ultisol Applied with Various Doses of Lime - Arsukman Edi; Jamilah Jamilah; Milda Ernita (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2023)
Indonesia has a wide area of acid-dry land with potential food crops, especially soybeans. The study was conducted to determine the effect of arbuscular mycorrhizal fungi (AMF) as seed coat of soybean on ultisol, applied with various doses of lime. The study was conducted in Ultisols in Kuranji Village, Kuranji District, Padang City, West Sumatra, Indonesia. The experiment was arranged in a split-plot design. The main plot was the dose of CaCO3 lime with two levels, namely 0 (without lime) and lime equivalent to 2 x Al-dd. Subplots were the application of seed coat in five ratios of AMF inoculant: former soybean planting soil, consisting of 0:4, 1:4, 2:4, 3:4, and 4:4. Each treatment was replicated three times. Data were analyzed for variance and the least significant difference (LSD) test with a significance level of 5%. The results showed that applying lime could increase P uptake in soybean plants by 25.58%. The highest soybean yield was 2.046 tons ha-1, yielded from seed coat treatment with a ratio of 2:4 without lime and the lime treatment equivalent to 2xAl-dd without seed coat.